Hombres, géneros y carretas: la circulación de bienes en la campaña bonaerense en la temprana época colonial - Montserrat, María Inés (Temas de historia argentina y americana, 2020)
The knowledge of the rural population of Buenos Aires during the XVIII century obtained from statistical sources can be expanded if complemented by other means of documentation. Non-statistical sources found in the Archivo General de Indias (Sevilla) have enabled a deeper analysis into the circulation of goods in the Buenos Aires countryside. The confiscations and the correspondence among officials provide interesting information about those settlers who transited - not always legally - the Pampas. This study seeks to analyze the activities of the rural population in an environment marked by fluvial boundaries, a not always visible population to enumerators, though circulating and dwelling into the countryside.